2019
DOI: 10.5194/acp-19-6419-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Arctic sulfate aerosol and clouds to changes in future surface seawater dimethylsulfide concentrations

Abstract: Abstract. Dimethylsulfide (DMS), outgassed from ocean waters, plays an important role in the climate system, as it oxidizes to methane sulfonic acid (MSA) and sulfur dioxide (SO2), which can lead to the formation of sulfate aerosol. Newly formed sulfate aerosol resulting from DMS oxidation may grow by condensation of gases, in-cloud oxidation, and coagulation to sizes where they may act as cloud condensation nuclei (CCN) and influence cloud properties. Under future global warming conditions, sea ice in the Arc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…Nitrate and silicic acid concentrations in the SML were limiting, with values below 0.6 and 0.9 µmol L −1 , respectively, indicating that most of the nutrients, initially present in the surface, had already been consumed by the primary producers. The exhaustion of nitrate in surface waters, the deepening of the nitracline, and the development of a SCM are typical features of summer conditions in several regions of the Arctic as demonstrated by a host of comprehensive investigations (Tremblay et al, 2008;Mundy et al, 2009;Martin et al, 2010;Ardyna et al, 2013;Brown et al, 2015;Steiner et al, 2015).…”
Section: The Fyi Edge In Barrow Strait and The Adjacent Lancaster Soundmentioning
confidence: 99%
“…Nitrate and silicic acid concentrations in the SML were limiting, with values below 0.6 and 0.9 µmol L −1 , respectively, indicating that most of the nutrients, initially present in the surface, had already been consumed by the primary producers. The exhaustion of nitrate in surface waters, the deepening of the nitracline, and the development of a SCM are typical features of summer conditions in several regions of the Arctic as demonstrated by a host of comprehensive investigations (Tremblay et al, 2008;Mundy et al, 2009;Martin et al, 2010;Ardyna et al, 2013;Brown et al, 2015;Steiner et al, 2015).…”
Section: The Fyi Edge In Barrow Strait and The Adjacent Lancaster Soundmentioning
confidence: 99%
“…Recent modelling studies have examined the impact of DMS on Arctic aerosols. Marelle et al (2017) updated the WRF-Chem regional model by adding DMS(g) and reported an improvement in surface sulfate estimates in the Arctic. Mahmood et al (2019) evaluated the impact of DMS(g) emission on the formation of sulfate aerosol, CCN and cloud radiative forcing in a global climate model.…”
Section: Introductionmentioning
confidence: 99%
“…Marelle et al (2017) updated the WRF-Chem regional model by adding DMS(g) and reported an improvement in surface sulfate estimates in the Arctic. Mahmood et al (2019) evaluated the impact of DMS(g) emission on the formation of sulfate aerosol, CCN and cloud radiative forcing in a global climate model. Although they did not find a significant increase in sulfate aerosol, they predicted higher nucleation rates, increased sulfate deposition and an increase in the cloud droplet number concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Marelle et al (2017) updated the WRF-Chem regional model by adding DMS(g) and reported an improvement of surface sulfate estimates in the Arctic. Mahmood et al (2019) evaluated the impact of DMS(g) emission on the formation of sulfate aerosol, CCN and cloud radiative forcing in global climate model. Although they did not find a significant increase of sulfate aerosol, they predicted higher nucleation rates, increased sulfate deposition, and an increase of cloud droplet number concentration.…”
Section: Introductionmentioning
confidence: 99%